2020
DOI: 10.1155/2020/3204285
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Characteristics of Moso Bamboo Micropile‐Composite Soil Nailing System in Soft Soil Areas

Abstract: Based on the characteristics of moso bamboo including high short-term strength, stable performance, and ability to provide temporary support for shallow foundation pits in soft soil, the stress characteristics and supporting effects of the ecological composite supporting system have been explored through model tests and numerical calculation analysis of the moso bamboo micropile-composite soil nailing structure. The results showed that the bamboo pile can effectively control the horizontal deformation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…e bridge pier of the model assumes stiffness equivalence [1,[13][14][15][16][17]. e section design of the bridge pier is strictly equivalent as per the bending stiffness, ignoring the torsional and axial stiffnesses.…”
Section: Shaking Table Testmentioning
confidence: 99%
See 1 more Smart Citation
“…e bridge pier of the model assumes stiffness equivalence [1,[13][14][15][16][17]. e section design of the bridge pier is strictly equivalent as per the bending stiffness, ignoring the torsional and axial stiffnesses.…”
Section: Shaking Table Testmentioning
confidence: 99%
“…e device considers the relative acceleration of the pier and beam as the control variable under the action of the earthquake, uses the rotational inertial force of the additional mass of the rotating shaft to activate the coiled cable, and generates greater friction by rubbing the coiled rope on the post such that the pier of the movable support can reach the instantaneous "fixed" state, as shown in Figure 3. Furthermore, the seismic response of the superstructure is borne by portable and fixed-bearing ports, which reduce the seismic response of the fixed-bearing piers and the longitudinal displacement of the beam ends to improve the seismic performance of continuous-girder bridges [14].…”
Section: Wrcd Designmentioning
confidence: 99%
“…In recent years, some researchers have conducted systemic research on lockup devices. However, these devices do not efectively reduce the seismic response of low piers [19,20]. Owing to the challenges in price and maintenance, they do not have several applications in practical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the shortcomings of the capillary theory, Tong et al proposed a rigid ice model that includes an area where ice and water coexist between the bottom surface of the warmest ice and the freezing front [7]. Cheng and Deng discovered a relationship between different ice potentials and the frost heaving rate of coarse-grained soil by studying the particle size, and he concluded that the smaller the particle size, the stronger the effect [8]. Wang et al conducted a lot of freezing tests of unsaturated soil, considering the influence of fine content and degree of saturation [9].…”
Section: Introductionmentioning
confidence: 99%